1999
DOI: 10.1159/000015241
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic assignment of 53 microsatellites from the USDA-MARC porcine genetic map

Abstract: This study provides 53 new fluorescent in situ hybridization cytogenetic assignments for microsatellite markers linked on the swine genetic map. Forty microsatellites are physically assigned for the first time. The chromosomal locations of eight markers were either confirmed or refined, while five loci were assigned to locations different from those given in previous reports. Markers were selected to provide physical anchors based on their presumed proximity to centromeres or telomeres and at approximately 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…Swine chromosome ideograms are shown beside the RH map. The correlation of the locations of TNFRSF6, TNFSF6 and the markers that are nearest to TNFRSF6 and TNFSF6 among those already mapped in both the cytogenetic map and the IMpRH map (SW2593 and SW2515 for TNFRSF6 and S0095 and SW1651 for TNFSF6 [Ellegren, 1993;Rohrer et al, 1996;Lopez-Corrales et al, 1999]) between the RH map and the cytogenetic map was also indicated in this figure to support the correctness of the location mapped based on our results.…”
Section: Fluorescence In Situ Hybridization (Fish)supporting
confidence: 86%
“…Swine chromosome ideograms are shown beside the RH map. The correlation of the locations of TNFRSF6, TNFSF6 and the markers that are nearest to TNFRSF6 and TNFSF6 among those already mapped in both the cytogenetic map and the IMpRH map (SW2593 and SW2515 for TNFRSF6 and S0095 and SW1651 for TNFSF6 [Ellegren, 1993;Rohrer et al, 1996;Lopez-Corrales et al, 1999]) between the RH map and the cytogenetic map was also indicated in this figure to support the correctness of the location mapped based on our results.…”
Section: Fluorescence In Situ Hybridization (Fish)supporting
confidence: 86%
“…Two-point analysis revealed close linkage of the EGFR gene to the microsatellites SW749 at a distance of 6.7 cR (LOD score 5.47) and SW1651 at a distance of 8.2 cR (LOD score 4.00). SW1651 has been physically assigned to SSC9q26 (Lopez-Corrales et al, 1999), which is in perfect accordance with the FISH result.…”
Section: Mapping Data: Lifrsupporting
confidence: 72%
“…A panel of 39 microsatellite loci distributed throughout the genome and identified as part of the Pig Genome Project was used in this study. The markers used (with chromosome position) were: S0073 (4), SW35 (4), S0298 (16), SW1134 (5), SW1851 (1), SW2456 (X/Y), SW2514 (2), SW983 (9), S0120 (18), SW2 (5), SW1557 (14), SW378 (5), SW761 (14), SW2008 (11), SW995 (5), SW352 (7), SW472 (7), SW949 (X/Y), S0004 (15), S0165 (3), S0217 (4), SW225 (13), SW1041 (10), SW21 (9), SW2404 (4), S0035 (6), S0006 (16), SW749 (9), SW2410 (8), SW940 (9), S0295 (9), SW839 (4), SW2406 (6), SW2419 (6), SW316 (6), S0121 (7), SW322 (6), S0385 (11) and SW2443 (2) (Fredholm et al, 1993;Ellegren et al, 1994;Hoyheim et al, 1994;McQueen et al, 1994;Robic et al, 1994;Rohrer et al, 1994;Groenen et al, 1995;Alexander et al, 1996;Rohrer et al, 1996;Lopez-Corrales et al, 1999).…”
Section: Methodsmentioning
confidence: 99%